(3ELGRI ef GdTjN eMeO Ljei ddTjN eMeO GdeQGHWs - (3GdeQGHW , eMeO Hf eMeO Hf YHO GdYRjR GdeQGHW GdSLdeGSj, CHh YHO Gddg,J (B1140 (3g` s
(3ChdgG (B:s
(3SeY GdTjN GdYdGeI SjOi eMeO GdeQGHW ef SjOi eMeO Mjej ef SjOi CHj HcQ GdOdGFi Hecg GdecQeI s
(3BNQgG (B:s
(3hCeG GdELGRI aGfJgJ HGdSjO GdePchQ hcGfJ efg HecI ai SfI CMO YTQ HYO GdCda hGddg CYde s
(3Vef eLehY , JQJjHgG (B: (3ef U (B124 - (3U(B125s
(3GdJhKjbGJ GdeQLYjI (B:s
(3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B11 - (3U (B234s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- (3bSe (B4 - (3U (B14 s
(3eUOQ GbJfGA GdCUd (B:s
(3GdQHGW (B(489 (3O(B) s
Keywords: (3GdJGQjNs